2015
DOI: 10.1515/biolog-2015-0191
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli expression of NDV fusion protein gene and determination of its antigenic epitopes

Abstract: Recurrent outbreaks of Newcastle disease have questioned the usage of existing vaccines that whether they are still adequate to protect clinical diseases and inhibit virus transmission in poultry. Advancement in molecular biology has led to the production of recombinant vaccines in recent years, which can be a more useful strategy to control infections of Newcastle disease virus (NDV). Studies indicate that the pathogenic nature of NDV is mediated by its membrane associated fusion (F) protein. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A comparison of the endpoint titers showed that there are not statistically significant differences. These results were in line with the findings of other researchers using similar epitopic or the full-length of F or HN protein for immunogenicity in the animal models (16, 17, 19). Furthermore, the detection of the HN and F glycoproteins with the individually produced antibodies revealed the potential application of these antibodies as probes for the viral glycoprotein in immunological analyses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A comparison of the endpoint titers showed that there are not statistically significant differences. These results were in line with the findings of other researchers using similar epitopic or the full-length of F or HN protein for immunogenicity in the animal models (16, 17, 19). Furthermore, the detection of the HN and F glycoproteins with the individually produced antibodies revealed the potential application of these antibodies as probes for the viral glycoprotein in immunological analyses.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is relatively limited information about the immunological properties of the recombinant surface glycoproteins of the NDV expressed in the E. coli system. There are a few reports about the successful expression and purification of NDV glycoproteins in the E. coli in which the recombinant HN was used as main the component in the ELISA based method (17) and purification of the immunogenic F protein that were studied elsewhere (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…the hN protein is the most important antigen that can induce a strong immune response. the hN protein is a capsid protein that attaches itself firmly to the viral membrane, thus making it very difficult to isolate and purify from infected cells (Shahid et al, 2015). immunization with recombinant hN protein has been attempted many times to study protective immune responses in chickens (Boursnell et al, 1990;Edbauer et al, 1990;Sun et al, 2008;Su et al, 2011).…”
Section: Discussionmentioning
confidence: 99%